A supercritical CO2 Brayton cycle with a bleeding anabranch used in coal-fired power plants. (1st January 2018) - Bai, Ziwei; Zhang, Guoqiang; Li, Yongyi; Xu, Gang; Yang, Yongping
Abstract: This study investigates a novel supercritical carbon dioxide Brayton cycle with a bleeding anabranch used in coal-fired power plants. For the proper utilization of the medium-low temperature heat in the boiler, the coupling between the air-preheater and the cycle is concentrated. After analyzing the distribution of heat duty in the boiler, the flow diagram of the Brayton cycle is design. Subsequently, the influences of maximal temperature/pressure, pinch temperature difference, component pressure drop, and preheated air temperature on the cycle efficiency are studied. Results show that the proposed cycle coupled with a coal-fired power plant can achieve 52.33% gross cycle efficiency and 49.5% net low heat value efficiency with 296 bar/650 °C. A further increment of 1% pt. in gross cycle efficiency can be achieved with the decrement of 5 K pinch temperature difference or 0.7 bar pressure loss in the recuperators. The simulation indicates that an increment of 2.14% pt. in gross cycle efficiency can be further achieved with 370 bar/700 °C. Besides, the parameter of the bleeding anabranch do not affect the cycle performance. In conclusion, this study proposes a promising novel supercritical carbon dioxide cycle coupled with coal-fired power plants. Highlights: A SCO2 Brayton cycle with bleeding anabranch for coal-fired power is proposed. The distribution of the boiler heat duty is analyzed to couple the Brayton cycle. The novel cycle is excellent in efficiency accompanying sensitivity analysis. The cycle configuration is flexible for a boiler to design its air preheater.